Frequency and antibiotic resistance of bacterial agents causing respiratory tract infections in adults - Bogdanović, Svetlana; Tončić, Danijela; Vacic, Nebojsa; Zlatković, Ivana; Gajević, Ivana (PONS - medicinski časopis, 2023)
Introduction. Acute respiratory infections (ARI) are the most common infectious diseases of the modern times, and among the ten leading causes of death at global scale. They have the highest mortality rates within the infective etiology, as the fourth leading cause of death in the world, with 2,603,913 cases in 2019. The goal of the paper. The goal of this paper was to define the most common organisms causing ARI, as well as their resistance to antibiotics in outpatients from the territory of town of Prokuplje. Material and methods. The analysis was performed retrospectively after six months of sampling. It included isolation and identification of bacterial agents of respiratory infections, as well as their resistance to certain antibiotics. Results and discussion. The studied sample, collected during the 6-month period, included 308 individual samples of throat swabs and 308 individual samples of nose swabs. Out of the total number of tested samples, pathogenic microorganisms were recorded in 43 samples of throat swabs (13.96%) and 107 samples of nose swabs (34.74%). The most common pathogen in nasal swab samples was Moraxella with 39.25%, followed by bacteria Haemophylus sp., St. aureus and S. pneumoniae with approximate values of 21.50%, 19.63% and 17.77%. As expected, the smallest value was recorded for Enterobacter sp. with 1.85%. The analysis of group resistance toward the tested antibiotics has shown that the most susceptible bacteria were Moraxella sp., as they failed to show complete resistance to any of the tested antibiotics. The highest levels of sensitivity were recorded toward gentamicin and ofloxacin. The greatest level of resistance was recorded for Haemophylus sp. which has shown resistance above 50% for all studied antibiotics except cefotaxime. Conclusion. The most common bacteries are Moraxella sp. i Haemophylus sp. Haemophylus sp. showed the highest level of resistancy, while highest level of sensitivity was Moraxella sp. in regard to group of tested antibiotics.